The economic impact of HIV/AIDS in Africa: with special emphasis on Botswana - Gwillim, Tyler F. (Kansas State University, 2009)
This essay on AIDS examines the possible economic impact HIV and AIDS can have on an economy. AIDS is a growing problem throughout the world and has become one of the worst pandemics of the 21st century. Africa is one of the worst hit regions in the world, having seven countries with more than 15 percent of the population infected. This essay will have special emphasis on Botswana where 37.3 percent of the population is infected. Botswana has had various negative micro-level economic impacts which have begun to spillover and negatively affect macro-level economics. The International Monetary Fund predicts GDP growth is expected to fall from 5.5 percent a year without AIDS to between 1.5 and 2.5 percent a year with AIDS. There are various sectors in an economy that can be impacted by AIDS. This essay will look at factors affecting these various sectors, explain them and describe what impact they are having on Botswana’s economy.
Keywords: Botswana; Africa; Aids; Economics, General (0501)